Biomechanical Comparison of 4 Transsacral Fixation Constructs in a Type 61C, Zone II Pelvic Fracture Model. Issue 10 (October 2022) - Bradley, Hallie; Pierce, Bill; O'Neill, David; Jo, Chan-Hee; Ahn, Junho; Farahani, Farzam; Greif, Charlotte; Sanders, Drew; Starr, Adam
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: OTA/AO 61C pelvic ring injuries are vertically unstable because of complete sacral fractures combined with anterior ring injury. The objective of this study was to compare the biomechanical characteristics of 4 transsacral screw constructs for posterior pelvic ring fixation, including one that uses a novel fixation method with a pair of locked washers with interdigitating cams. Methods: Type C pelvic ring disruptions were created on 16 synthetic pelvis models. Each pelvis was fixated with an S2 screw in addition to being allocated to 1 of 4 transsacral constructs through S1: (1) 8.0-mm screw, (2) 8.0-mm bolt, (3) 8.0-mm screw locked with a nut, and (4) 8.00-mm screw locked with a nut with the addition of interdigitating washers between the screw head and ilium on the near cortex, and ilium and nut on the far cortex. The anterior ring fractures were not stabilized. Each pelvis underwent 100, 000 cycles at 250 N and was then loaded to failure using a unilateral stance testing model. The anterior and posterior osteotomy sites were instrumented with pairs of infrared (IR) light-emitting markers, and the relative displacement of the markers was monitored using a three-dimensional (3D) motion capture system. Displacement measurements at 25, 000; 50, 000; 75, 000; and 100, 000 cycles and failure force were recorded for each pelvis. Results: The novel washer design construct performed better than the screw construct with less posterior ring motion at 75, 000 ( P = 0.029) and 100, 000 cycles ( P = 0.029). Conclusions: The novel interdigitating washer design may be superior to using a screw construct alone to achieve rigid, locked posterior ring fixation in a synthetic pelvis model with a Type C pelvic ring disruption.